2011
DOI: 10.1002/jms.1957
|View full text |Cite
|
Sign up to set email alerts
|

MALDI‐TOFMS analysis of coordination and organometallic complexes: a nic(h)e area to work in

Abstract: A mini-review of the characterisation of metal-containing compounds by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOFMS) is presented. Organometallic and coordination compounds have many varied applications, most notably in industrial catalytic processes and also in the electronics and healthcare sectors. In general, the compounds discussed, be they small or large molecules, have a high percentage metal content, rather than simply containing 'a metal atom'. A brief hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 95 publications
1
23
0
Order By: Relevance
“…68 The applications of MALDI for offline analysis of a variety of small molecule and biological processes are legion, and these studies are too numerous to review here. Instead, we will focus on the development and specific use of MALDI as a tool to intercept reaction intermediates and study mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…68 The applications of MALDI for offline analysis of a variety of small molecule and biological processes are legion, and these studies are too numerous to review here. Instead, we will focus on the development and specific use of MALDI as a tool to intercept reaction intermediates and study mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…It is based on the detection of the intact molecular ion as gas ionic species, which sometimes is quite hard to get from organometallic compounds . Several ionization techniques have been attempted for the analysis of these complexes by MS . However, most of those trials showed disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of LDI or MALDI ionization in the condensed phase, the majority of complexes gave simple and interpretable mass spectra (Wyatt, Stein, and Brenton 2006;Wyatt 2011). However, direct photochemical degradation and other photochemical reactions in course of LDI and MALDI ionization reduced the abundance of molecular ions in favor of fragments.…”
Section: Introductionmentioning
confidence: 98%